Sponge-supported monolithic materials of porphyrin covalent organic frameworks for selective recognition, convenient removal and extraction of Cd2+. Issue 3 (June 2022) - Jin, Wei-Liang; Li, Wei; Wang, Hai-Xian; Liu, Xiao-Wei; Jiang, Hong-Xin; Zhu, Li-Na; Kong, De-Ming
Abstract: Adsorption is a cheap, energy-efficient, and easy-to-operate method for heavy metal pollution treatment. As highly porous and crystalline polymers, covalent organic frameworks (COFs) hold great promise as the adsorbents of metal ions. Herein, two hydroxyl-functionalized porphyrin COFs (2, 3-DhaTph and 2, 5-DhaTph) were synthesized, characterized and demonstrated to be good adsorbents of cadmium(II) ion (Cd 2+ ). Via the chemical coordination of abundant phenolic hydroxyls to Cd 2+ and the fluorescent response of porphyrin moieties to Cd 2+, 2, 3-DhaTph realized bifunction of specific optical recognition and highly efficient adsorption of Cd 2+ . To further simplify the removal operation of Cd 2+, bulk monolithic materials (PS@COFs) were prepared via the in-situ growth of 2, 3-DhaTph or 2, 5-DhaTph on the pore wall of a dopamine-treated heat-resistant polyurethane sponge. Compared to the COFs, PS@COFs showed faster adsorption kinetics and shorter adsorption equilibrium time due to the interconnected large porous channels and the uniform distribution of thin COF layer on the pore wall. The characteristics of easy operation and good reusability (≥ 6 times) endow PS@COFs with great potential in practical applications, more than 99% Cd 2+ could be easily removed from water samples by them. PS@COFs were also demonstrated to work well for the extraction of various heavy metal ions from polluted food samples (rice and wheat), achieving the detection of these metal ions. Graphical Abstract: ga1 Highlights: Two hydroxyl-functionalized porphyrin COFs and corresponding sponge-supported monolithic materials are prepared. The bifunction of specific optical recognition and highly efficient adsorption of Cd 2+ is realized. Different Cd 2+ coordination modes of the two COFs are discussed. The monolithic materials exhibit faster adsorption kinetics and shorter adsorption equilibrium time than COFs. The monolithic materials work well for Cd 2+ removal from water samples and Cd 2+ extraction for polluted rice and wheat samples.